2017
DOI: 10.1016/j.ejmp.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 18F-FDG-PET image reconstruction algorithms on the expression of characteristic metabolic brain network in Parkinson’s disease

Abstract: PURPOSE To evaluate the reproducibility of the expression of Parkinson’s Disease Related Pattern (PDRP) across multiple sets of 18F-FDG-PET brain images reconstructed with different reconstruction algorithms. METHODS 18F-FDG-PET brain imaging was performed in two independent cohorts of Parkinson’s disease (PD) patients and normal controls (NC). Slovenian cohort (20 PD patients, 20 NC) was scanned with Siemens Biograph mCT camera and reconstructed using FBP, FBP+TOF, OSEM, OSEM+TOF, OSEM+PSF and OSEM+PSF+TOF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…In this study, we compared data from different centers. It is well-known that variations in PET scanners and image reconstruction algorithms influence disease-related pattern scores [53][54][55] (supplementary Fig 1). In support of this, we recently identified clear center-specific features in the current data using machine-learning algorithms [56].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we compared data from different centers. It is well-known that variations in PET scanners and image reconstruction algorithms influence disease-related pattern scores [53][54][55] (supplementary Fig 1). In support of this, we recently identified clear center-specific features in the current data using machine-learning algorithms [56].…”
Section: Discussionmentioning
confidence: 99%
“…However, the widespread implementation of such SSM/PCA-derived disease-related metabolic brain patterns in multicenter collaborations and clinical practice has been hindered by differences between PET scanners as well as acquisition and reconstruction protocols. Variations in scanners and image reconstruction algorithms have been shown to systematically shift image quality and disease-related pattern subject scores [6] , [24] , [25] , [26] .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that PDRP topography was highly reproducible across FDG‐PET reconstruction algorithms. In addition, within each type of reconstruction per scanner, discrimination between patients and HCs was not significantly impacted when using disease‐related patterns derived using the same reconstruction method, whereas calibration with HCs was advised when different methods were used [25,26]. However, the impact of additional variables on PDRP expression scores, such as histogram glucose uptake intensity distribution across voxels, as well as image contrast, has not yet been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Tomse P. et al [25] evaluated the reproducibility of the expression of Parkinson's Disease Related Pattern (PDRP) across multiple sets of 18F-FDG-PET brain images reconstructed with different reconstruction algorithms. Their results showed that the expression of PDRP was reproducible across a variety of reconstruction algorithms of 18 F-FDG-PET brain images and so PDRP is capable of providing a robust metabolic biomarker of Parkinson's disease for multi centre 18 F-FDG-PET images acquired in the context of differential diagnosis or clinical trials.…”
Section: Nuclear Medicinementioning
confidence: 99%